2019
DOI: 10.1109/tit.2019.2917425
|View full text |Cite
|
Sign up to set email alerts
|

On the Sub-Packetization Size and the Repair Bandwidth of Reed-Solomon Codes

Abstract: Reed-Solomon (RS) codes are widely used in distributed storage systems. In this paper, we study the repair bandwidth and sub-packetization size of RS codes. The repair bandwidth is defined as the amount of transmitted information from surviving nodes to a failed node. The RS code can be viewed as a polynomial over a finite field GF (q ℓ ) evaluated at a set of points, where ℓ is called the sub-packetization size. Smaller bandwidth reduces the network traffic in distributed storage, and smaller ℓ facilitates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 36 publications
(115 reference statements)
2
32
0
Order By: Relevance
“…MSR vector codes are well studied in [10], [38]- [44], where each symbol is a vector. As one of the most popular codes in practical systems, Reed-Solomon (RS) code and its repair is studied in [11], [45]- [48], where each symbol is a scalar.…”
Section: Flexible Msr Codesmentioning
confidence: 99%
See 2 more Smart Citations
“…MSR vector codes are well studied in [10], [38]- [44], where each symbol is a vector. As one of the most popular codes in practical systems, Reed-Solomon (RS) code and its repair is studied in [11], [45]- [48], where each symbol is a scalar.…”
Section: Flexible Msr Codesmentioning
confidence: 99%
“…Let B be the base field of F such that F = B L . For repairing RS codes, [45] and [48] shows that any linear repair scheme for a given RS(n, k) over the finite field F = B L is equivalent to finding a set of repair polynomials p * ,v (x) such that for the failed node…”
Section: Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…• more than two errors in information symbol: In this case the complexity of procedures quantified by Υ 1I , Υ 2I , Υ 1P 1I can be added as the worst case: (16,6,23,9,2). (106)…”
Section: Complexity Estimation Of the Algorithmmentioning
confidence: 99%
“…More surprisingly, in recent years a new interest in these codes has risen in the research community. It is caused by the fact that they are extensively used in cloud technology, namely in distributed storage systems [5,6,7,8,9]. In [1] it was shown that RS codes could be extended not only three times, but even five times when they are constructed over certain finite fields.…”
Section: Introductionmentioning
confidence: 99%